2023
DOI: 10.3390/plants12051025
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination of Three Milk Thistle (Silybum marianum (L.) Gaertn.) Populations of Greek Origin: Temperature, Duration, and Storage Conditions Effects

Abstract: Milk thistle besides being a highly competitive weed is cultivated as a medicinal plant, and the seeds of which have been clinically utilized in several disorders caused in liver. The present study aims to evaluate the effect of duration and storage conditions, population, and temperature on seed germination. The experiment was conducted in Petri dishes with three replications and three factors: (a) wild populations of milk thistle (Palaionterveno, Mesopotamia, and Spata) originating from Greece, (b) duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[119], downy brome (Bromus tectorum L.) [120], capeweed (Arctotheca calendula (L.) K. Lewin) [121], night-flowering catchfly (Silene noctiflora L.) [6], and milk thistle (Silybum marianum (L.) Gaertn.) [122]. In some cases, however, dry storage decreases germination percentage, as was shown for sea oats (Uniola paniculate L.) [123], European hazelnut (Corylus avellana L.) [124], and snow gum (Eucalyptus pauciflora Sieber ex Spreng.)…”
Section: The Effects Of Post-dispersal Factors On Seed Dormancy: Afte...mentioning
confidence: 86%
“…[119], downy brome (Bromus tectorum L.) [120], capeweed (Arctotheca calendula (L.) K. Lewin) [121], night-flowering catchfly (Silene noctiflora L.) [6], and milk thistle (Silybum marianum (L.) Gaertn.) [122]. In some cases, however, dry storage decreases germination percentage, as was shown for sea oats (Uniola paniculate L.) [123], European hazelnut (Corylus avellana L.) [124], and snow gum (Eucalyptus pauciflora Sieber ex Spreng.)…”
Section: The Effects Of Post-dispersal Factors On Seed Dormancy: Afte...mentioning
confidence: 86%
“…Seed longevity decreases with storage [37] and can usually be judged by the color of the seed coat, which loses its luster, while the germination potential, germination rate, and germination index also decrease when seeds are stored for a long time [38,39]. In this study, we found that the germination potential, germination rate, and germination index of E. villosa seeds decreased significantly during eight years of storage, and the determination of E. villosa seed vigor by the TTC method was consistent with germination test results.…”
Section: Discussionmentioning
confidence: 99%
“…MGT = ∑ (ni × di)/N, where ni—number of seeds germinated a day, N—total number of germinated seeds at the end of experiment 44 .…”
Section: Methodsmentioning
confidence: 99%